Pleiotropic role of Drosophila phosphoribosyl pyrophosphate synthetase in autophagy and lysosome homeostasis - Delos Santos, Keemo (PLoS Genet, 2019)
Phosphoribosyl pyrophosphate synthetase (PRPS) is a rate-limiting enzyme whose function is important for the biosynthesis of purines, pyrimidines, and pyridines. Importantly, while missense mutations of PRPS1 have been identified in neurological disorders such as Arts syndrome, how they contribute to neuropathogenesis is still unclear. We identified the Drosophila ortholog of PRPS (dPRPS) as a direct target of RB/E2F in Drosophila, a vital cell cycle regulator, and engineered dPRPS alleles carrying patient-derived mutations. Interestingly, while they are able to develop normally, dPRPS mutant flies have a shortened lifespan and locomotive defects, common phenotypes associated with neurodegeneration. Careful analysis of the fat body revealed that patient-derived PRPS mutations result in profound defects in lipolysis, macroautophagy, and lysosome function. Significantly, we show evidence that the nervous system of dPRPS mutant flies is affected by these defects. Overall, we uncovered an unexpected link between nucleotide metabolism and autophagy/lysosome function, providing a possible mechanism by which PRPS-dysfunction contributes to neurological disorders.